Sensitive detection of dengue virus type 2 E-proteins signals using self-assembled monolayers/reduced graphene oxide-PAMAM dendrimer thin film-SPR optical sensor - Sheh Omar, Nur Alia; Fen, Yap Wing; Abdullah, Jaafar; Mustapha Kamil, Yasmin; Mohd Daniyal, Wan Mohd Ebtisyam Mustaqim; Sadrolhosseini, Amir Reza; Mahdi, Mohd Adzir (Nature Publishing Group, 2020)
In this work, sensitive detection of dengue virus type 2 E-proteins (DENV-2 E-proteins) was performed in the range of 0.08 pM to 0.5 pM. The successful DENV detection at very low concentration is a matter of concern for targeting the early detection after the onset of dengue symptoms. Here, we developed a SPR sensor based on self-assembled monolayer/reduced graphene oxide-polyamidoamine dendrimer (SAM/NH2rGO/PAMAM) thin film to detect DENV-2 E-proteins. Surface characterizations involving X-ray diffraction (XRD) and Fourier-transform infrared spectroscopy (FTIR) confirms the incorporation of NH2rGO-PAMAM nanoparticles in the prepared sensor films. The specificity, sensitivity, binding affinity, and selectivity of the SPR sensor were then evaluated. Results indicated that the variation of the sensing layer due to different spin speed, time incubation, and concentration provided a better interaction between the analyte and sensing layer. The linear dependence of the SPR sensor showed good linearity (R2 = 0.92) with the lowest detection of 0.08 pM DENV-2 E-proteins. By using the Langmuir model, the equilibrium association constant was obtained at very high value of 6.6844 TM−1 (R2 = 0.99). High selectivity of the SPR sensor towards DENV-2 E-proteins was achieved in the presence of other competitors.